Europe's exports superstar: It's the organisation! - Dalia Marin; Jan Schymik; Jan Tscheke (Bruegel, 2015)
What explains Germany's superb export performance? Is Germany's export behaviour very distinct compared to other European countries? We explore the organisational responses to competition of 14,000 exporting firms in seven European countries. We examine the export business model of the median exporter and of the top one percent exporters in each country, accounting for 20 percent to 55 percent of total exports. What do these firms do to become superstars? We find, first, that the export market share of the median exporter in each of the countries to the world more than tripled (in some cases the export market share increases tenfold) for firms that combine decentralised management with offshoring of production to low-wage countries. Exporters which abstain from any organisational adjustment do very badly. Decentralised management provides incentives for workers for product improvements allowing exporters to compete on quality. Offshoring production to low-wage countries reduces costs allowing exporters to compete on price. Second, we find that Germany is the leading quality exporter in Europe followed by Austria and Spain. Among the top 10 percent of exporters there is no single firm with low quality in Germany and Austria, which suggest that decentralised management has provided incentives for quality in these countries. Third, Germany's exports are less vulnerable to price increases, while exports from France and Italy respond strongly to price changes, and thus costs reductions via offshoring benefits these countries most.
Keywords: 330